The combination of the blood based tumor biomarkers cytokeratin 19 fragments (CYFRA 21-1) and carcinoembryonic antigen (CEA) as a potential predictor of benefit from adjuvant chemotherapy in early stage squamous cell carcinoma of the lung (SCC) - Muley, Thomas; Warth, Arne; Schneider, Marc; Dienemann, Hendrik; Meister, Michael; Herth, Felix (Lung cancer, 2018)
Objectives - To determine whether the tumor biomarkers cytokeratin 19 fragment (CYFRA 21-1) and carcinoembryonic antigen (CEA), which are prognostic in early-stage non-small cell lung cancer (NSCLC), can predict which patients benefit from adjuvant chemotherapy (CTx). - Materials and methods - Serum samples were collected preoperatively from patients with NSCLC who underwent resection. Samples were retrospectively analyzed for CYFRA 21-1 and CEA via electrochemiluminescence immunoassay. Recurrence-free survival (RFS) was compared for patients who received adjuvant CTx versus surgery alone, stratified based on the following prognostic classifications: (1) tumor stage (pT1‐2/N0 [stage I] or pT3/N0 or pT1‐2/N1 [stage II]), (2) biomarker-based risk score, (3) clinical characteristics. Absolute 2-year RFS rates were calculated via Kaplan-Meier estimations; statistical significance level: 0.05. - Results - 227 patients were included (stage I: 69%; male: 67%; median age 65 years); 70 received adjuvant CTx. Median duration of sample collection was 58.8 months. All high-risk patients (by all three prognostic classifications) who received adjuvant CTx had a longer RFS versus those who received surgery alone. In patients with squamous cell carcinoma (SCC) classified as high risk by all three prognostic classifications, there was a benefit from adjuvant CTx versus surgery alone (tumor stage hazard ratio [HR] 4.9, p=0.004; biomarker levels HR 9.4, p=0.002; clinical characteristics HR 9.0, p=0.003). None of the prognostic classifications were able to predict a benefit from adjuvant CTx in patients with adenocarcinoma. - Conclusion - Baseline CYFRA 21-1 and CEA levels may provide further information to help clinicians decide which patients with SCC should receive adjuvant CTx. Further evaluation of these biomarkers is warranted.